A segurança em territórios turísticos: o caso do município de Inhambane em Moçambique - Azevedo, Helsio Amiro Motany de Albuquerque (2014)
The safety, security and tourism are concepts that must keep engaged in the process of tourism planning and management to value the landscape of tourist territory. Security, as part of the tourist offer, should not be ignored in the process of development of territories, because they may lose the image quality and the benefits from the sector, which can install the chaos and unprecedented way to valorize or devaluate the landscape. This study aimed to show the importance of safety for the development of tourism at Inhambane municipality (IM) in Mozambique. In a time that tourist demands are more exigent and qualified and the competition bigger between the tourist destinations, the activities of planning the territory through studies of touristic offer, are crucial, to public and private managers. Through bibliographic and documental review, the use of questionnaires and interviews, observation and a workshop, sought information’s that supported the theoretical construction of tourist safety and also elucidate the real situations of tourist destinations that experienced by weakness in its security systems. Mozambique and the IM are not far from this reality, because the study demonstrated that there are problems in the tourism planning and management, in general, and specifically in the tourism safety. It is understood that the IM and Mozambique are destinations that can see their efforts doomed to failure if in short and medium time, the managers of tourism, not incorporate, into their planning and management, specific actions that contribute to improving the quality of tourist offer. Political and military conflicts and the exposure of the territory to extreme events in the territories, as the cyclones, for example, associated with the lack of resources and weak preparedness of private and public managers are the main risks that could "undermine" the tourism development specifically and local development in general. The situations described support the thesis that the stakeholders in the tourism sector, in Inhambane municipality, ignore the tourist safety as a key element for providing positive social and spatial dynamics, situation that will lead the tourism sector to failure.